Strategic perils of outsourcing: Sourcing strategy and product positioning - Noriaki Matsushima; Cong Pan (Osaka University, Institute of Social and Economic Research (ISER), 2016)
Although outsourcing input production has long been considered as an important approach to help downstream manufacturers enhance structural efficiency, we provide a theoretical explanation for why outsourcing may negatively affect downstream firms' profitability. We consider a duopoly model wherein downstream manufacturers endogenously determine their input sourcing and product positioning strategies. We show that when inputs from outside suppliers are not perfectly compatible with downstream manufacturers' requests, outsourcing causes downstream manufacturers to pursue aggressive product positioning behavior, leading to the prisoner's dilemma - even though both downstream manufacturers could be better off producing inputs in-house, they may still choose outsourcing.
Keywords: C72; L13; M31; 330; Outsourcing; Product differentiation; Suppliers; Hotelling model